Polymerase chain reaction (PCR). Description of the method and its application in the detection of viruses - PAPANASTASSOPOULOU (Μ. ΠΑΠΑΝΑΣΤΑΣΟΠΟΥΛΟΥ) M. (Journal of the Hellenic Veterinary Medical Society, 2018)
Since the first publication of the polymerase chain reaction (PCR) in 1985, there has been a large number of reports on its applications in the study of viral infections. This review outlines the PCR methodology and its variations, as well as the problems that may be encountered during its performance. Its application in the detection of various viruses in clinical samples is also presented.